Problems of the historical continuity of state system of the Golden Horde and the Kazakh Khanate (Journal of history, 2017)
In this article, the problems of historical continuity of the state system of the Golden Horde and the Kazakh Khanate were considered. Medievists thoroughly studied the history of the state structure of each state separately, that is, the principles of continuity and succession were not the focus of scientists. In the course of the investigation of the aforementioned problem, we adhered to precisely these principles. The historical-comparative analysis was used. The study of such elements of the state system as the ulus, the division of the army into two wings, the belonging of the khan's power to the Chingizids both in the Golden Horde and in the Kazakh Khanate led us to the conclusion that the historical continuity of the state system between these states really existed.